Clinical validation of the upper face first principle—A clinical, prospective, interventional split‐face study. (27th December 2022) - Hernandez, Claudia A.; Zapata, David E. Uribe; Bermudez, Maria Paula; Frank, Konstantin; Moellhoff, Nicholas; Alfertshofer, Michael; Gotkin, Robert H.; Davidovic, Kristina; Cotofana, Sebastian
Abstract: Background: Previous clinical and anatomic investigations have identified the clinical relevance of facial biomechanics. Based on this new understanding, principles for facial aesthetic procedures were established: Lateral Face First, Deep Layers First, and Upper Face First. Objective: To test the upper face first principle by showing that an injection sequence, starting in the upper face is superior to an injection sequence starting in the lower face. Methods: This study was designed as an interventional split‐face study administering the same amount and type of soft tissue filler for the upper, middle, and lower face but in a different sequence: upper, middle, lower face versus lower, middle, and upper face. A total of 15 patients (5 males and 10 females) with a mean age of 39.4 years (9.6) and a mean BMI of 23.4 kg/m 2 (1.7) were studied. Follow‐up at D0, D30, and D90 was conducted utilizing semiquantitative scores and objective 3D imaging. Results: Despite not reaching statistical significance, midfacial volume and jawline contouring were rated better at every follow‐up visit (D0, D30, D90) when treated with the upper versus the lower face first injection algorithm. The global aesthetic improvement scale showed statistically significantly better values for the upper face first algorithm when compared to the lower face first algorithm at all evaluated time points with all p < 0.001. Conclusion: Applying the upper face first injection algorithm seems to result in better aesthetic outcomes when directly compared to the lower face first algorithm. Semiquantitative and objective outcome measurements confirm its clinical effectiveness.